1997
DOI: 10.1097/00001888-199708000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Stress and depressed mood in medical students, law students, and graduate students at McGill University

Abstract: Medical students are not greatly stressed relative to other groups, hence other explanations must be sought for the elevated levels of depression in some students. One situation in which stress appears to be particularly important is in the transition from basic science training to clinical training. Targeted interventions may be an effective way of dealing with this problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
106
1
10

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(129 citation statements)
references
References 0 publications
12
106
1
10
Order By: Relevance
“…In an auxiliary question, this study also examines the question of whether medical students are also more exposed than students of other disciplines. There are still unclear findings here [1921]. …”
Section: Introductionmentioning
confidence: 91%
“…In an auxiliary question, this study also examines the question of whether medical students are also more exposed than students of other disciplines. There are still unclear findings here [1921]. …”
Section: Introductionmentioning
confidence: 91%
“…Surprisingly, doing regular exercise was not an independent correlate although it is deemed to reduce stress [2]. These independent correlates of perceived stress emphasize the need for adjusting for personal and environmental factors in studies dealing with stress: first, trait personality, then coping strategies and stress triggers [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…The medical program is viewed as a stressful environment [15]. However, few studies have compared academic programs and even some failed to confirm this statement [16,17]. The discrepancy in results has been explained by the instruments used to measure stress, some of which were not validated [16,17].…”
Section: Résumémentioning
confidence: 99%
“…14,15,16 While some studies have found little or no evidence of stress among medical students. 17,18 IJBAR (2013) 04 (11) www.ssjournals.com…”
Section: Discussionmentioning
confidence: 99%